Tailored deformation behavior of 304L stainless steel through control of the crystallographic texture with laser-powder bed fusion. (July 2022) - Sofras, C.; Čapek, J.; Arabi-Hashemi, A.; Leinenbach, C.; Frost, M.; An, K.; Logé, R.E.; Strobl, M.; Polatidis, E.
Graphical abstract: Highlights: Manipulation of the crystallographic texture of 304L stainless steel with Laser-Bed Powder Fusion. Enhancement of the martensitic transformation and twinning effects by tailoring the crystallographic textures. Assessment of asymmetric deformation behavior between tension and compression, through the Effective Stacking Fault Energy. Revealing the effect of the evolving crystallographic texture on the deformation behavior. Abstract: Laser-powder bed fusion (L-PBF) has gained significant research interest, not only for its profound advantage of producing near-net shape complex geometries of metallic parts, but also for the possibility of producing tailored microstructures. Here we exploit the capability of manipulating the crystallographic texture by L-PBF to tailor the deformation behavior of austenitic stainless steels. In specific, by adjusting the laser power and the laser scanning speed, tailored crystallographic textures can be obtained, along the uniaxial loading direction in 304L stainless steel samples produced by L-PBF. In situ neutron diffraction and uniaxial tension and compression tests are undertaken to investigate the extent of the transformation induced plasticity effect and to correlate it with the tailored macrostructures. The influence of the initial and the evolving crystallographic texture on the deformation behavior is demonstrated and elaborated accordingly. The observed asymmetry in the deformation behavior between tension and compression is also discussed in detail.